The Evaluation of Medical Device Interaction Based Prototype Verification System Using Human Operator Model - Priyanka, R; Sivakumar, R (International Journal of Computer Sciences and Engineering, 2025)
We present a formal check approach for recognizing plan issues related to client interaction, with a center on client interface of restorative devices. The approach makes a novel use of arrangement charts proposed by Rushby to formally check essential human variables properties of client interface implementation. In particular, it first deciphers the programming execution of client interface into an equivalent formal specification, from which a behavioral model is developed utilizing hypothesis proving; human variables properties are then confirmed against the behavioral model; lastly, an exhaustive set of test inputs are produced by exploring the behavioral model, which can be utilized to challenge the certifiable interface execution and to guarantee that the issues recognized in the conduct model do apply to the implementation. We have prototyped the approach based on the PVS verification system, and connected it to examine the client interface of a certifiable restorative device. The investigation recognized several collaboration plan issues in the device, which may conceivably lead to serious consequences.